Pengaruh Perilaku Etis Penjual terhadap Loyalitas Pelanggan, Kepuasan, dan Kepercayaan dalam Industri Pakaian - Soepartono, Sekar Ayu Putri; Arafah, Willy (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study examines the relationship between ethical sales behavior, customer satisfaction, and customer loyalty. Utilizing a conceptual model developed based on CRM and ECSI theories, the research shows that ethical sales behavior has a positive impact on customer satisfaction and loyalty. Additionally, customer satisfaction is proven to have a positive effect on customer loyalty. Customer trust is identified as a variable that influences loyalty and positively impacts customer satisfaction. The results of this study affirm that ethical sales behavior contributes to customer loyalty through customer satisfaction and trust. These findings provide important practical implications for organizations to enhance customer loyalty by improving ethical sales behavior and meeting customer needs.